2002
DOI: 10.4269/ajtmh.2002.67.151
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of hepatitis B virus (HBV) genotypes B and C in Japanese patients with chronic HBV infection.

Abstract: Abstract. The aims of this retrospective survey were to determine the epidemiologic distribution of hepatitis B virus (HBV) genotypes and analyze the genotype-related clinical differences among Japanese patients with chronic HBV infection. The 158 surveyed patients with chronic HBV infection lived in Fukuoka and Okinawa were serially tested for serum alanine aminotransferase (ALT) and hepatitis B e antigen (HBeAg). Follow-up was for a period of 10.8 ± 6.4 years (mean ± SD). The HBV genotypes were determined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 36 publications
4
34
2
Order By: Relevance
“…There have been several reports concerning the comparison between genotypes C and B in Asia. It is reported that HBV genotype B is associated with earlier HBeAg seroconversion than genotype C or that genotype C is associated with more severe liver disease than genotype B [Kao et al, 2000;Orito et al, 2001a;Chu et al, 2002;Furusyo et al, 2002;Sumi et al, 2003]. There have also been some reports concerning the comparison between genotypes A and D in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports concerning the comparison between genotypes C and B in Asia. It is reported that HBV genotype B is associated with earlier HBeAg seroconversion than genotype C or that genotype C is associated with more severe liver disease than genotype B [Kao et al, 2000;Orito et al, 2001a;Chu et al, 2002;Furusyo et al, 2002;Sumi et al, 2003]. There have also been some reports concerning the comparison between genotypes A and D in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were negative for hepatitis C serological markers, but all had detectable HBV surface antigen (HBsAg) for at least 6 months prior to the start of entecavir therapy. Two patients received 0.01 mg entecavir and one patient received 0.1 mg entecavir for 24 weeks, prior to 0.5 mg/day from a phase II study ETV-047 in Japan [11]. The other patients received 0.5 mg entecavir.…”
Section: Study Populationmentioning
confidence: 99%
“…The status of the HBeAg and anti-HBe antibody correlated with that of mutations in precore regions. Most patients infected with genotype B showed the precore mutation before the age of 30 years, absence of HBeAg production, followed by reduction in HBV-DNA levels (32).…”
Section: -1 Clinical Differences Of Hbv Genotypesmentioning
confidence: 99%